2019
DOI: 10.1002/jor.24267
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐loaded mineral‐coated microparticles improve bone repair and are associated with increased expression of epo and RUNX‐2 in murine non‐unions

Abstract: A poor vascular supply of the fracture gap is a key factor for the development of atrophic non‐unions. Mineral‐coated microparticles (MCM) represent a sophisticated carrier system for the delivery of vascular endothelial growth factor (VEGF). Hence, we investigated whether VEGF‐loaded MCM improve bone repair in non‐unions. For this purpose, we analyzed binding and release kinetics of MCM for VEGF in vitro. Moreover, we applied VEGF‐loaded or ‐unloaded MCM in a murine non‐union model in vivo and studied the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…More importantly, vascular supply at the fracture site is an essential step in the healing process since a good blood supply means plenty of the oxygen and nutrients required for fast healing [54]. Furthermore, the key physiological regulator of angiogenesis during embryogenesis and skeletal growth is VEGF [54,55]. A previous study revealed that FM stimulates angiogenesis in the wound site, enhancing tendon healing [23].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, vascular supply at the fracture site is an essential step in the healing process since a good blood supply means plenty of the oxygen and nutrients required for fast healing [54]. Furthermore, the key physiological regulator of angiogenesis during embryogenesis and skeletal growth is VEGF [54,55]. A previous study revealed that FM stimulates angiogenesis in the wound site, enhancing tendon healing [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible approach analyzed by others may represent the use of single growth factors such as VEGF or PDGF to enhance healing. 40,41 However, due to high costs and strict regulations, the use of single growth factors in addition to BSM is not implemented up-to-date in the clinical pathway. The main prerequisites for ideal BSM are both ease of its handling and application as well as biological characteristics close to autologous bone.…”
Section: Discussionmentioning
confidence: 99%
“…Its local application in bone defects has already been shown to successfully increase vascularization and bone formation. 133,[137][138][139][140][141] BMP-2 on the other hand, despite its ability of inducing bone formation, 142 lacks the capacity to initiate angiogenesis. 143 However, another protein from the BMP family, BMP-7, induces early graft remodeling by stimulating blood vessel formation and osteoclastic activity, as well as the expression of angiogenic and inflammatory cytokines.…”
Section: Local Growth Factor-based Vascularization Strategiesmentioning
confidence: 99%
“…The technique of the local delivery of those substances ranges from the direct injection into the fracture area, 140 the coating of scaffolds and bone allografts with growth factors, 134,135 the application of hydrogel formulations, microspheres, and microparticles loaded with specific cytokines [137][138][139]157,165 to the transfection with proangiogenic gene vectors. [166][167][168][169] The geneactivated matrix concept, for instance, involves the preloading of matrices with gene vectors to guarantee a sustainable release of DNA to ingrowing cells at the fracture site.…”
Section: Local Growth Factor-based Vascularization Strategiesmentioning
confidence: 99%